Pengaruh Kepemilikan Institusional, Ukuran Perusahaan, Leverge Terhadap Manajemen Laba(Studi Empiris Pada Perusahaan Manufaktur Yang Terdaftar Di Bei Tahun 2010-2013) - Hermato, Wawan, Drs. Yuli Tri Cahyono , M.M., Akt., CA (2015)
Earning management is a shape of the report manipulation of the profit which is done by management to achieve certain goal by playing the posts of income and the cost of profit -loss. The purpose of this research is to analyze the influence of the institusional ownership, company size, and leverage toward earning management. The method of collecting the sampel by using purposive sampling appropriate with the criteria has been decided. The total of samples collected is 280 companies. The total of out liner is 124 companies. Thus, the samples becomes 156 companies. The tool of analyzing that is used is doubel linear regression by using the data annual reportduring 2010-2013 periods on manufacture companies in IDX. The results of this research is that the institutional ownership and company size affected (statistically significant) toward earning manage, while leverage cannot be affected ( statistically not significant) toward earning management. Key words: company size, institutional ownership, leverage, earning management.